2010
DOI: 10.1002/mrc.2592
|View full text |Cite
|
Sign up to set email alerts
|

Relative acidities and structure analysis of cis and trans isomers of 1,5‐oxazaspiro[5.5] undecane derivatives by multinuclear magnetic resonance

Abstract: The relative acidities of the cis and trans isomers of a series of 1,5-oxazaspiro[5.5]undecane derivatives were determined by measuring DeltapK in acid-base titrations followed by (1)H NMR. Relative structural stabilities were determined by measuring substituent chemical shift and gamma-gauche effects in (13)C, (15)N, and (17)O NMR. Crystallographic characterization of a model spiro[5.5]undecane is presented to support the basicity in solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Relative structural stabilities were determined by measuring substituent chemical shift and g-gauche effects in 13 C, 15 N and 17 O NMR. 314 315 A number of signals in the NMR spectrum of the B1 domain of streptococcal protein G (GB1) show a chemical shift dependence on the concentration of the protein at pH = 3 but not at neutral pH, implying the existence of selfassociation at low pH. Analysis of relaxation dispersion experiments yields a self-association constant of 50 mM, and shows that 15 N chemical shift changes in the dimer interface are up to 3 ppm.…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 97%
See 1 more Smart Citation
“…Relative structural stabilities were determined by measuring substituent chemical shift and g-gauche effects in 13 C, 15 N and 17 O NMR. 314 315 A number of signals in the NMR spectrum of the B1 domain of streptococcal protein G (GB1) show a chemical shift dependence on the concentration of the protein at pH = 3 but not at neutral pH, implying the existence of selfassociation at low pH. Analysis of relaxation dispersion experiments yields a self-association constant of 50 mM, and shows that 15 N chemical shift changes in the dimer interface are up to 3 ppm.…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 97%
“…Relative structural stabilities were determined by measuring substituent chemical shift and g-gauche effects in 13 C, 15 N and 17 O NMR. 422 To clarify the positive role of sidechain conformation in the stability of protein secondary structure (mainchain conformation), the authors successfully calculated the optimisation structure of a series of well-defined a-helical octadecapeptides composed of two L-phenylalanine (Phe) and 16 L-alanine (Ala) residues, based on the MO calculation with density functional theory (DFT/B3LYP/6-31G(d)). Furthermore, the authors demonstrated that the 1 H, 13 3 and rutherfordine (UO 2 CO 3 ) is presented, the former representing a system with a hydrogen-bonding environment around the uranyl oxygens and the latter exemplifying a uranyl environment without hydrogens.…”
Section: 16mentioning
confidence: 99%